PENGARUH STATEGI ULA TERHADAP TINGKAT TEKANAN DARAH PADA HIPERTENSI LANSIA DI PUSKESMAS GODONG II (STIKES Telogorejo Semarang, 2023)
Elderly is someone who has reached the age of 60 years and over. The elderly are a group that is included in the vulnerable category, as a vulnerable group. The elderly have the characteristics of various changes in all aspects of life which include physiological, psychological, social and spiritual changes. Hypertension is a chronic condition without symptoms in which the arterial blood pressure is very high. So prevention of further hypertension can be done by using the following strategy (measure blood pressure regularly, continue to take medication regularly and recommend drinking traditional herbs). This study aims to determine the effect of the ULA strategy on hypertension blood pressure levels in the elderly. This type of research uses a pre-experiment one group pre-post test design. The sampling technique used was accidental sampling with a total of 30 respondents. The statistical test used is Wilcoxson. From the results of this study, 25 respondents obtained ULA strategy data that routinely intervened, while the mean artery prausure (MAP) 2 respondents occupied stage 1, 7 respondents occupied stage 3 and 19 respondents occupied stage 4. The results of this study indicate that there is a significant influence between before and after being given the intervention with a p value: 0.000 (<0.005). Recommendations from the results of the study are that the ULA strategy can be used as an intervention to reduce blood pressure levels.